Potential for cross-contamination of diatom DNA samples when using toothbrushes - Martyn G. Kelly (Pensoft Publishers, 2021)
The use of toothbrushes and similar devices for sampling diatoms from hard surfaces is a well-established approach. Toothbrushes are routinely cleaned and reused when sampling for analysis by light microscopy. This paper looks at the scale of contamination encountered when this technique is used to sample diatoms for metabarcoding analyses, as well as at the scale of contamination to be expected if stream, rather than distilled water, is used to wash diatoms from stones. Although some contamination attributable to toothbrushes was detected, read numbers were low and had no effect on index calculation or ecological status estimates. However, if the primary focus of a study is to thoroughly document diversity in a sample, then even this small level of contamination may be unacceptable and more stringent measures may be required.